Solid waste generation from the hotel industry in the coastal tourism cities of Vietnam - Thi Hoa Tran; Boris Fabres; Ngoc Ha Hoang; Hoai Le Tran (Vietnam Journal of Science, Technology and Engineering, 2022)
While the tourism and hospitality sectors in Vietnam have been rapidly developing, the increasing consumption of natural resources and production of associated waste, especially in coastal and island sites, threaten these marine areas with pollution. This study provides data on solid waste from 10 hotels in three coastal provinces of Vietnam, namely, Hai Phong, Quang Nam and Phu Yen. The results indicated significant percentages and volumes of organic waste especially from large-scale hotels with in-house food services like restaurants and bars. The proportions of organic and recyclable solid waste from all three surveyed cities ranged between 35- 84% and 10-27%, respectively. Plastic waste accounted for a relatively high proportion of solid waste ranging from 27 to 60% total solid waste by volume and from 7 to 30% by weight. In particular, PET plastic made up the highest proportion of solid waste in Cat Ba town (52.41%) and Tuy Hoa city (39.81%) while singlelayer plastic accounted for the highest proportion (29.55%) in Hoi An city. Plastic waste from food packaging, related to the cultural habits of guests that bring instant food items during their stay, was identified as an important issue, which reflects a valuable but presently wasted potential resource. These quantities of hotel solid waste can be recovered and provide additional environmental and health benefits to the community by not being dumped, landfilled, or openly burned.